The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1978
DOI: 10.1002/sce.3730620210
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feedback on questioning of preservice teachers in SCIS microteaching

Abstract: Providing feedback to preservice teachers about their teaching style is an important component of most performance-based teacher education models. In these models it is assumed that if preservice teachers are provided a critique of their ability to perform a certain teaching behavior in a specific microteaching setting, then the teachers will be able to improve their ability to perform that behavior in subsequent teaching assignments. Interest has been shown by a number of researchers about whether the source … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…As feedback was not provided to students, wait-time I was probably reduced by student talk. Esquivel et al (1978) reported that feedback on wait-time II did not lead to increased wait-time over a sequence of three science lessons. The results of a pilot study conducted by Swift!…”
Section: Synthesis Of Wait-time Researchmentioning
confidence: 97%
“…As feedback was not provided to students, wait-time I was probably reduced by student talk. Esquivel et al (1978) reported that feedback on wait-time II did not lead to increased wait-time over a sequence of three science lessons. The results of a pilot study conducted by Swift!…”
Section: Synthesis Of Wait-time Researchmentioning
confidence: 97%
“…Although the body of research on in-service education and teacher change is quite large, there appears to be a scarcity of research that deals specifically with science teacher education programs (Evans, 1987). A number of studies present evidence that training that involves a questioning classification or strategy analysis system can be instrumental in changing the behavior of preservice teachers (Esquivel, Lashier, & Smith, 1978;Riley, 1978;Tobin, 1985;Yeany, 1977). In-sentice training in specific behaviors such as questioning (Bruce, 1971;Otto & Schuck, 1983) and wait time (Chewprecha, Gardner, & Sapianchai, 1980;Swift & Gooding, 1983) can also be effective in changing teacher behaviors.…”
mentioning
confidence: 99%